Water-sediment partitioning of flumequine and florfenicol, two antibiotics used in salmon aquaculture in Chile - Jara, Bibiana; Srain, Benjamín M.; Aranda, Mario; Fernández, Camila; Pantoja-Gutiérrez, Silvio; Méjanelle, Laurence (Marine pollution bulletin, 2022)
The water-sediment partitioning of flumequine and florfenicol, two antibiotics used in salmon aquaculture is a critical driver of their fate and environmental impact. Batch experiments, were carried out using pure water or seawater, with or without sediment, and at summer and winter temperatures of Chilean fjords. Log Kd (partition between water and sediment) of florfenicol in seawater varied from 0.62 ± 0.69 to 0.67 ± 0.13, and Log KOC (partition between water and organic fraction of sediment) from 2.15± 0.29 to 2.19 ± 0.13. Difference between KOC and the octanol-water partition constant (KOW) showed that for florfenicol, adsorption onto the surface of particles was more significant than the absorption driven by hydrophobicity whilst hydrophobic absorption was a major driver of flumequine sorption. Flumequine Log Kd (0.92 ± 0.25 to 1.36 ± 0.10) and Log KOC (from 2.44 ± 0.25 to 2.89 ± 0.10) demonstrated its greater affinity than florfenicol to particles and potential accumulation into marine sediments. [Display omitted] •Flumequine has a greater affinity for sediment particles than florfenicol.•In seawater, 11 ± 5% of florfenicol and 24 ± 7% of flumequine are sorbed to particles.•Surface-driven processes control the sorption of florfenicol (KOC)< KOW).•Hydrophobic absorption drivesi dissolved-particle partition of flumequine (KOC ≈ KOW)•The formation of complexes with seawater ions lowers florfenicol concentration by 13 ± 8% with respect to Milli-Q water.